PERANCANGAN DOKUMEN HIRARC DI AREA PRODUKSI DAN GUDANG BESAR PABRIK ICE CREAM HONGKONG CV. SUMBER REJEKI - CM William Gan; Kriswanto Widiawan (Jurnal Titra, 2021)
One of the problems in the Hong Kong ice cream factory is work accidents, the absence of K3 management makes the handling of K3 cases not done properly. Designing a Hazard Identification Risk Assessment and Risk Control (HIRARC) document is a way to help Hong Kong ice cream factories deal with K3 problems. The design of the HIRARC document begins with direct observations and interviews with factory residents, besides that the author also asks for OHS data from the company if any. Risk assessment and analysis of the case findings obtained, to determine what activities are high risk so that risk control is carried out immediately. Risk control is a suggestion from the author and the result of the approval of the factory management. The results of this final project result in hazard identification, risk assessment, and risk control on findings that have a medium risk rating, and reduce the risk level from medium to low.